The Analysis of Social Factors of Code-Mixing Used in The Movie “The Guys” By Raditya Dika - Aqsha, Alivia Saudia; Zaim, M. (English Language and Literature, 2024)
Code-mixing is the combination of two languages that have different linguistic elements within communication. This study aims to analyze the social factors influencing the use of code-mixing in the movie “The Guys” by Raditya Dika. The research employs Muysken's (2000) theory to identify three types of code-mixing: Insertion, Alternation, and Congruent Lexicalization. Furthermore, the research uses Bhatia and Ritchie's (2013) theory to identify four social factors: Participant Role, Situational Factors, Message-Intrinsic Factors, and Language Attitudes, Dominance, and Security. The data were categorized into different types and social factors influencing code-mixing in the movie's utterances. The research findings are expected to provide insights into the types of code-mixing frequently used in everyday conversations, as well as the social factors influencing the use of code- mixing in the utterances of “The Guys” (2017). Based on the data analysis, the researcher found 86 instances of code-mixing in this film. The findings show that this research is dominated by Insertion, with 73 (82%), and Situational Factor with 56 (36%).